ANALISIS KESESUAIAN TINGKAT KETERBACAAN CERITA ANAK DENGAN KEMAMPUAN MEMBACA PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SD - Akmal Fauzi; Moza Aristina; Nadia Herina Putri; Rahmatul Hawiyah; Zenia Putri Yanche; Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the suitability of the readability level of children’s stories with the reading abilities of fifth-grade elementary school students in Indonesian language learning. The study used a qualitative descriptive approach with a literature review method. Data were collected from various scientific sources such as journals, articles, and previous studies related to readability, children’s literature, and students’ reading comprehension. The results showed that the readability level of children’s stories has a significant relationship with students’ reading comprehension abilities. Texts with readability levels that match students’ cognitive development and literacy skills are easier to understand and can increase reading interest, comprehension, and active participation in learning. Conversely, texts with inappropriate readability levels tend to cause difficulties in understanding the content, reduce motivation, and lower students’ reading interest. In addition, factors such as learning media, reading habits, and teaching methods also influence students’ reading comprehension. Therefore, teachers need to consider readability aspects when selecting and developing children’s story materials so that the learning process becomes more effective and meaningful.